Foldable/Expandable Gastro-retentive Films Based on Starch and Chitosan as a Carrier For Prolonged Release of Resveratrol - Boontawee, Rattakorn; Issarachot, Ousanee; Kaewkroek, Kanidta; Wiwattanapatapee, Ruedeekorn (Current Pharmaceutical Biotechnology, 2022)
Background: Resveratrol exerts a number of therapeutic effects, notably antiinflammatory, antioxidant and anti-cancer activities which are beneficial for the treatment of gastric diseases. However, the efficacy of resveratrol is severely limited due to the poor aqueous solubility and rapid metabolism following oral administration. As a result, foldable/expandable devices based on natural polymers merging with solid dispersion technology have been developed to increase the solubility, prolong the gastric residence time, and provide a controlled release therapy of resveratrol. Objectives: This research aimed to invent foldable/expandable films based on natural polymers, including starch and chitosan, for stomach-specific delivery and prolonged release of resveratrol. Methods: The films were prepared by solvent casting using either rice, tapioca, corn starch or pregelatinized corn starch combined with chitosan in different weight to weight ratios. Glycerol was included as a plasticizer. Resveratrol solid dispersions (Res-SD) prepared by solvent evaporation and employing PVP-K30 as a hydrophilic polymer were loaded into the polymeric film, which was subsequently folded prior to insertion in a hard gelatin capsule. Results: The solid dispersions improved the solubility of resveratrol by a factor of 500. All Res-SD loaded film formulations completely unfolded in simulated gastric fluid at 37oC within 10 min. Fluid absorption by the films was influenced by the ratio of amylose and amylopectin in the starch granules, with tapioca starch formulations displaying the highest fluid uptake. Films prepared from pregelatinized corn starch and chitosan resulted in highly efficient delivery of resveratrol, with more than 80%of the content released over a period of 12 hrs. Furthermore, the released polyphenol exhibited cytotoxic activity against human gastric adenocarcinoma cells and anti-inflammatory effects against lipopolysaccharide-stimulated murine, macrophage-like cells. Conclusions: These findings demonstrate the potential of foldable/expandable films based on natural polymers as a promising stomach-specific carrier for improving the treatment of gastric disorders.
Keywords: Resveratrol